The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/solr.202100295
|View full text |Cite
|
Sign up to set email alerts
|

Defect Passivation of Perovskite Films for Highly Efficient and Stable Solar Cells

Abstract: Perovskite solar cells (PSCs) have been introduced as an attractive photovoltaic technology over the past decade due to their low‐cost processing, earth‐abundant raw materials, and high power conversion efficiencies (PCEs) of up to 25.2%. However, the relatively high density of defects within the bulk, grain boundaries, and surface of polycrystalline perovskite films acts as recombination centers and facilitates ion migration, lowering the theoretical PCE ceiling, often leading to inferior device stability. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 280 publications
(453 reference statements)
2
60
0
Order By: Relevance
“…The mixed A‐cation LHP NCs can be synthesized directly using the mixture of desired A‐cation precursors or by applying post‐synthetic A‐cation exchange and cross‐exchange on pre‐synthesized mono‐cation LHP NCs, as illustrated in Figure . The direct synthesis can be carried out by classical methods such as hot‐injection [ 48–175 ] or reprecipitation [ …”
Section: Mixed A‐cation Halide Perovskite Ncsmentioning
confidence: 99%
“…The mixed A‐cation LHP NCs can be synthesized directly using the mixture of desired A‐cation precursors or by applying post‐synthetic A‐cation exchange and cross‐exchange on pre‐synthesized mono‐cation LHP NCs, as illustrated in Figure . The direct synthesis can be carried out by classical methods such as hot‐injection [ 48–175 ] or reprecipitation [ …”
Section: Mixed A‐cation Halide Perovskite Ncsmentioning
confidence: 99%
“…Many studies report that significant changes occur in perovskite films during illumination or application of bias, including halide segregation, ion migration, and compositional degradation due to defect states on the surface and bulk or grain boundaries of perovskite films. ,, On the other hand, it has been demonstrated that defect states can spread out irreversibly under humid conditions due to severe degradation. , Therefore, an efficient device encapsulation can suppress these negative behaviors in PSCs at long-term illumination and applied bias.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Generally, an ideal additive, depending on its functional group, should have an effective chemical interaction with perovskite components to improve the quality of thin films. 57,58 Firstly, pyrazine was added to tin-based perovskite precursor as a co-additive with SnF 2 to suppress the Sn 2+ oxidation and homogeneous dispersion of SnF 2 in the thin film by forming the SnF 2 –pyrazine complex. 59 The SnF 2 –pyrazine complex forms by strong d → π* back-donation coordination from tin( ii ) halide to the pyrazine ring.…”
Section: Tin-based Perovskitesmentioning
confidence: 99%